Integrated Moloney murine leukemia virus DNA studied by using complementary DNA which does not recognize endogenous related sequences. - Bacheler, L T (1980)
By preannealing a radioactive, representative Moloney murine leukemia virus (M-MuLV) cDNA with large excesses of AKR 70S viral RNA, an M-MuLV-specific cDNA has been prepared. When hybridized to restriction enzyme fragments of M-MuLV-infected mouse cell DNA, the preannealed probe recognizes integrated M-MuLV DNA and does not recognize endogenous related DNA sequences found in uninfected mouse cells. The viral DNA sequences recognized by the preannealed probe are spread throughout the viral genome, although some sequences are recognized less efficiently. By using this preannealed probe, multiple integrations of M-MuLV DNA have been detected in infected fibroblasts and in an M-MuLV-induced tumor. Integrated viral DNA fragments smaller than the complete viral genome have also been detected. By using this preannealed probe to examine a mass-infected culture of mouse fibroblasts, no evidence for a strongly preferred site for M-MuLV integration could be found.